A Model of Dual Educational System Organization in the 21st Century of Schools under the Secondary Education Affiliated with the Regional Education Office 13 - Kamphong, Thanvarith; Kotta, Priwan; Masena, Chuankid (Ratchaphruek Journal, 2024)
The objective of this research was to propose a Dual Educational System Organization Model for the 21st century for schools under the Secondary Education Affiliated with the Regional Education Office 13 by employing a multi-phase mixed methodology. The samples were: 1) 134 participants, selected through stratified random sampling, comprising school administrators, education system coordinators, teachers, and basic education committee members from secondary schools affiliated with the Regional Education Office 13; 2) four best practice schools in Dual Educational System Organization, purposively sampled; and 3) nine experts, purposively sampled for focus group discussions, comprising university professors, educational administrators, school administrators, and supervisors. Research instruments included questionnaires, interviews, and a model evaluation form. Data analyses involved percentages, averages, standard deviations, priority needs index, and content analysis. Results indicated that: 1) both overall and in all aspects, evaluations of the current conditions were at a high level, respectively, while both overall and in all aspects, evaluations of the proposed model were at the highest level, respectively; and 2) the model of Dual Educational System Organization in the 21st century for schools under Secondary Education affiliated with the Regional Education Office 13 consists of 5 components, namely, 2.1) principles, 2.2) objectives, 2.3) procedures, 2.4) evaluation, and 2.5) conditions for success. The confirmation results for both the suitability and feasibility of the model were at the highest level.